2015 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology (WI-IAT) 2015
DOI: 10.1109/wi-iat.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Persuasion with Dynamic Group Formation for Collaborative Elderly Care

Abstract: Ageing in place demands a new paradigm of inhouse caregiving allowing many aspects of daily lives to be tackled by smart appliances and technologies. The important challenges include the effective provision of recommendations by multiple parties of caregiver constituting changes of the user's behavior. In this multiagent environment, interdependencies between agents become major issues to tackle. This paper presents an approach of dynamic group formation for autonomous caregiving agents to collaborate in recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Randomized trial [2,3,11,48,55,56] Pilot study [12,13,14,21,26,31,35,39,40,43,44,45,46,47,53,54] Observational study [28,30] Preliminary studies for assessing usability or codesign choices [1,5,9,15,18,20,23,24,27,34,49] System proposal (no user study) [6,16,17,19,22,25,29,36,52] Study protocol [4,7,8,32,33,41] Field study [10,…”
Section: Type Of Study Papersmentioning
confidence: 99%
See 4 more Smart Citations
“…Randomized trial [2,3,11,48,55,56] Pilot study [12,13,14,21,26,31,35,39,40,43,44,45,46,47,53,54] Observational study [28,30] Preliminary studies for assessing usability or codesign choices [1,5,9,15,18,20,23,24,27,34,49] System proposal (no user study) [6,16,17,19,22,25,29,36,52] Study protocol [4,7,8,32,33,41] Field study [10,…”
Section: Type Of Study Papersmentioning
confidence: 99%
“…In fact, among the 56 papers selected as eligible for the analysis, five reported results of randomized controlled trials [2,3,11,55,56] and one study was a clinical trial [48], six reported protocols for future randomized trials [4, 7, 8, 32, 33, 41], 16 presented results of pilot studies [12,13,14,21,26,31,35,39,40,43,44,45,46,47,53,54] and two were observational studies [28,30], while [38] presented a pre-post intervention study. Eleven presented the results of a preliminary assessment of a system in terms of usability or co-design choice [1,5,9,15,18,20,23,24,27,34,49], four [10,42,50,51] presented a field study for deriving the requirements of a coaching system, and nine presented only a proposal of a coaching system or an architectural implementation, without any user study [6,16,17,19,22,…”
Section: Type Of Study Papersmentioning
confidence: 99%
See 3 more Smart Citations